2016
DOI: 10.4162/nrp.2016.10.4.442
|View full text |Cite
|
Sign up to set email alerts
|

A study on blood lipid profiles, aluminum and mercury levels in college students

Abstract: BACKGROUND/OBJECTIVESCollege students are in a period of transition from adolescence to adulthood, in which proper dietary habits and balanced nutritional intake are very important. However, improper dietary habits and lifestyles can bring several health problems. This study was performed to investigate blood lipid profiles, blood aluminum and mercury in college students and the relationships among them.SUBJECTS/METHODSThe subjects were 80 college students (43 males and 37 females) in Gyeonggi-do. General char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…For Hg exposed rats, the plasma Hg levels, after oral exposure were 35.41 ± 2.60 µg/L which was higher than levels found in several populations. Plasma Hg levels were reported to be an average of 3.08 ± 1.55 µg/L for a Korean male college population (n=43) [31] and 4.6 ± 3.0 µg/L for a larger population of Korean males (n=4283). [32] In an Egyptian population, Hg levels were 4.4 -12.1 µg/L, [28] and in a South African population 0.1 -8.82 µg/L.…”
Section: Resultsmentioning
confidence: 99%
“…For Hg exposed rats, the plasma Hg levels, after oral exposure were 35.41 ± 2.60 µg/L which was higher than levels found in several populations. Plasma Hg levels were reported to be an average of 3.08 ± 1.55 µg/L for a Korean male college population (n=43) [31] and 4.6 ± 3.0 µg/L for a larger population of Korean males (n=4283). [32] In an Egyptian population, Hg levels were 4.4 -12.1 µg/L, [28] and in a South African population 0.1 -8.82 µg/L.…”
Section: Resultsmentioning
confidence: 99%
“…The GM of blood Al was 10.57 μg/L, with no significant difference between men and women and no age dependence. A previous study reported that the GM of blood Al was 8.61 μg/L for college students in Korea [ 22 ]. However, blood Al levels measured here, were considerably higher than those reported in France (2.32 μg/L) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute and chronic exposure to aluminum chloride (AlCl 3 ) produced dyslipidemic changes, showing a significant increase in total cholesterol (TC), TG, and LDL with decreased HDL and a decrease in TC/HDL and LDL/HDL ratios. [ 7 8 9 ] College-going male students reported an incidence of dyslipidemia linked with increased Al levels in their blood. [ 8 ] A specific dyslipidemic pattern has been linked to the hormonal changes associated with menopause.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 8 9 ] College-going male students reported an incidence of dyslipidemia linked with increased Al levels in their blood. [ 8 ] A specific dyslipidemic pattern has been linked to the hormonal changes associated with menopause. These are accountable for cardiovascular deaths and associated complications linked with disrupted estrogenic activity.…”
Section: Introductionmentioning
confidence: 99%